Potassium-free catalyst and method for preparing p-methylstyrene with low water-hydrocarbon ratio

By combining active metals and additive metals on the γ-Al2O3 support, a potassium-free catalyst was prepared, which solved the problems of high energy consumption and short catalyst life under low water-hydrogen ratio conditions, and achieved an efficient and environmentally friendly dehydrogenation reaction of methyl ethylbenzene.

CN119500159APending Publication Date: 2025-02-25XIAN CATALYST NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411610194.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing Fe-K-Ce series catalysts have high energy consumption and short catalyst life in the dehydrogenation reaction of methyl ethylbenzene, especially under low water-hydrocarbon ratio conditions, there are irreversible inactivation problems caused by K loss and migration.

Method used

An iron-laden γ-Al2O3 was used as a support, combined with active metals such as Ti, Ga, Ce and other additive metals such as Ca, Mg, Zn, and Mo to prepare a potassium-free catalyst. The catalyst prepared Fe-Al2O3 support by hot oil column molding, and mixed and dissolved metal salts in the acid solution, added polyethylene glycol 2000 and citric acid to form a heterometal coordination complex, and finally prepared by pressurized crystallization.

Benefits of technology

It achieves high activity and selective catalyzing p-methylethylbenzene dehydrogenation under low water-hydrocarbon ratio conditions, extends the service life of the catalyst, avoids inactivation caused by K loss, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130739360000071
    Figure BDA0005130739360000071
  • Figure BDA0005130739360000072
    Figure BDA0005130739360000072
  • Figure BDA0005130739360000081
    Figure BDA0005130739360000081
Patent Text Reader

Abstract

The invention discloses a potassium-free catalyst and method for preparing p-methylstyrene with a low water-hydrocarbon ratio, the catalyst takes Fe-modified gamma-Al2O3 prepared by an oil column forming method as a carrier, and active metal and auxiliary metal are loaded through autoclave crystallization. Transition metal Fe is introduced in the technological process of preparing the gamma-Al2O3 carrier through a hot oil column forming method, after other metal salts are dissolved in an acid solution, polyethylene glycol and citric acid are added to serve as adhesion promoters, and active metal and auxiliary metal are loaded through a pressurized stirring crystallization method, so that the specific surface area of the catalyst is effectively increased, and the specific surface area of the catalyst is increased. The dispersity of the loaded metal is improved, and the interaction between the metal and the Fe-Al2O3 carrier is enhanced. A methyl ethylbenzene dehydrogenation reaction result of the prepared catalyst shows that a target product can be prepared under the condition that the water-hydrocarbon ratio is as low as 0.8, and the catalyst is good in catalytic performance, high in stability, remarkable in technical and economic effects and beneficial to industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a p-methylethylbenzene dehydrogenation catalyst, in particular to a potassium-free catalyst for catalyzing the dehydrogenation of p-methylethylbenzene to prepare p-methylstyrene under the operating conditions of a relatively low water-to-hydrocarbon ratio. Background Art

[0002] Para-methylstyrene is mainly used as a raw material for organic synthesis and can be used to prepare chemical intermediates such as methyl acrylate and methyl acetate. As a rubber additive, it can be used to improve the anti-aging properties of rubber and can also be used to synthesize chemical products such as dyes, coatings, and plastics. Compared with styrene, para-methylstyrene has a higher boiling point and lower vapor pressure, which can significantly reduce potential hazards. Polypara-methylstyrene is a new type of styrene-based plastic developed abroad in recent years. Compared with polystyrene, polypara-methylstyrene has a lower density, a higher deformation temperature, better fluidity, etc., and has a wider application space.

[0003] The main technical route for preparing alkyl styrene from alkyl aromatics is to use water vapor as a diluent and metal oxides as catalysts at normal pressure or low pressure. The early dehydrogenation catalysts for methyl ethylbenzene were mainly Cr-based catalysts, which had low catalyst efficiency and were harmful to the environment. They have now been replaced by Fe-K-Ce series catalysts, which are more active than methyl ethylbenzene, not only environmentally friendly but also have longer catalyst life. Since the dehydrogenation reaction of methyl ethylbenzene is a typical endothermic reaction, low pressure and high temperature are conducive to improving the conversion rate. In the industry, water vapor is introduced into the reaction process to promote the equilibrium to move to the right, slow down coking and dilute the reaction system to increase the yield of methyl styrene. However, a large amount of water vapor leads to high energy consumption. In addition, K, as the main auxiliary agent, can increase the catalyst activity by more than one order of magnitude, but as the amount of water vapor increases, K will slowly lose and migrate, which is one of the main reasons for the irreversible deactivation of the catalyst. Patents US4804799 and US5376613 invented ethylbenzene dehydrogenation catalysts with low potassium content, which effectively improved the yield of styrene, but under the condition of high-temperature water vapor, the catalyst life needs to be further improved. The catalyst invented in patent CN105562024A is suitable for reaction conditions with a low water-to-hydrocarbon ratio (1.6:1), which greatly reduces energy consumption, but there is still irreversible deactivation of the catalyst caused by K loss and migration. Therefore, it is urgent to develop a new environmentally friendly and efficient catalyst that can maintain or improve the performance of the catalyst under low or no water conditions, so as to meet the requirements of high-efficiency and long-term operation of the methyl styrene production unit. Summary of the invention

[0004] In order to solve the problems of high energy consumption and short catalyst life of the current industrial Fe-K-Ce series catalysts when used for the dehydrogenation of methylethylbenzene, the present invention provides a potassium-free catalyst for preparing methylstyrene with a low water-to-hydrocarbon ratio, which has high activity and selectivity, long service life and low energy consumption under high temperature and water vapor conditions.

[0005] The potassium-free catalyst for preparing p-methylstyrene at a low water-to-hydrocarbon ratio provided by the present invention is a γ-Al2O3 catalyst loaded with iron. 2 O 3 The catalyst is a carrier that carries active metals and auxiliary metals; the active metals are any one or more of Ti, Ga, and Ce, and the auxiliary metals are any one or more of Ca, Mg, Zn, and Mo; in terms of the mass percentage of the catalyst, the mass content of the active metals is 0.1% to 2%, the mass content of the auxiliary metals is 0.1% to 1.2%, and the mass content of Fe is 0.3% to 1%.

[0006] The preparation method of the catalyst provided by the present invention comprises the following steps:

[0007] Step 1: Mix low sodium pseudo-boehmite with an acid solution, stir at 60-80° C. for 2-3 hours to obtain a crude aluminum sol; add a non-polar solvent to the crude aluminum sol, stir at room temperature for 1-2 hours, then heat to 40-50° C. at a heating rate of 1-3° C. / min, stir at a constant temperature for 30-50 minutes, and stand for 10-18 hours to obtain an aluminum sol; at room temperature, add a gelling agent to the aluminum sol and continue to stir for 1-2 hours, then add an aqueous solution of an Fe precursor thereto, continue to stir for 1.5-2 hours, and adjust the pH of the system to 3-4 with a 10% hydrochloric acid aqueous solution to obtain an Fe-modified aluminum sol; adopt a hot oil column molding method to subject the Fe-modified aluminum sol to a ball dropping, aging, water washing, drying, and roasting process to obtain an iron-loaded γ-Al 2 O 3 , denoted as Fe-Al 2 O 3 carrier.

[0008] Step 2: Dissolve the active metal precursor and the auxiliary metal precursor in a 0.1 mol / L hydrochloric acid aqueous solution, add polyethylene glycol 2000 and citric acid, and ultrasonicate for 30 to 60 minutes to form a heterometallic coordination complex, pour into a high-pressure reactor with stirring and a PTFE lining, and then add the Fe-Al 2 O 3 The carrier is stirred and crystallized at a pressure of 1.5-2.0 MPa and a temperature of 150-180° C. for 10-24 hours. The obtained product is dried, calcined, and reduced in a hydrogen atmosphere to obtain a catalyst.

[0009] In the above step 1, the mass ratio of the low-sodium pseudo-boehmite to the acid solution is preferably 1:1.1-1.5, the acid solution is an aqueous solution of any one of hydrochloric acid, nitric acid, acetic acid, and chloroacetic acid, and the mass concentration of the acid solution is 8%-15%.

[0010] In the above step 1, the volume ratio of the crude aluminum sol to the non-polar solvent is preferably 1:1-3; the non-polar solvent is any one of toluene, carbon tetrachloride, and n-heptane.

[0011] In the above step 1, the gelling agent is preferably at least one of hexamethylenetetramine, urea, polyethylene glycol 2000, and sodium carboxymethyl cellulose; and the amount of the gelling agent added is 5% to 10% of the mass of the aluminum sol.

[0012] In the above step 1, the Fe precursor is ferric nitrate.

[0013] Furthermore, in the above step 1, the Fe-modified aluminum sol is formed by a hot oil column molding method, and is aged for 24 to 36 hours in a nitrogen atmosphere at 2 to 2.5 MPa and 140 to 170° C., washed with water to remove surface oil stains, dried at 100 to 150° C., and calcined at 750 to 850° C. for 3 to 5 hours to obtain an iron-loaded γ-Al 2 O 3 The Fe-Al 2 O 3 The specific surface area of ​​the carrier is 120-150m 2 / g, pore size is 14-17nm, and particle size is 1.6-1.8mm.

[0014] In the above step 2, the active metal precursor and the auxiliary metal precursor are nitrates of the corresponding metals, and preferably the added amounts of polyethylene glycol 2000 and citric acid are respectively Fe-Al 2 O 3 0.5%~2% and 1.5%~3% of the carrier mass.

[0015] In the above step 2, preferably, the calcination temperature is 400-600° C., and the calcination time is 2-6 hours; the reduction temperature is 350-450° C., and the reduction time is 2-5 hours.

[0016] The present invention also provides a method for preparing p-methylstyrene by dehydrogenating p-methylethylbenzene, which comprises: loading the catalyst of the present invention in a fixed bed reaction device, using p-methylethylbenzene as a raw material, carrying out a dehydrogenation reaction of p-methylethylbenzene in the presence of water vapor, the reaction temperature being 550-650° C., the reaction pressure being normal pressure, and the liquid space velocity being 0.5-5 h -1 The mass ratio of water vapor to p-methylethylbenzene (referred to as the water-hydrocarbon ratio) is 0.5 to 3:1.

[0017] The present invention introduces transition metal Fe into the process of preparing alumina carrier by hot oil column molding to obtain Fe-modified γ-Al 2 O 3 As a carrier, the metal salt is mixed and dissolved in an acid solution, polyethylene glycol 2000 and citric acid are added, and the metal salt is completely dissolved by ultrasound to form a heterometallic coordination complex, and the catalyst is prepared by pressure crystallization. Compared with the prior art, the beneficial effects of the present invention are as follows:

[0018] 1. The catalyst of the present invention is a non-Cr catalyst and is more environmentally friendly than the current industrial Fe-K-Ce series catalysts.

[0019] 2. The catalyst carrier in the present invention is Fe-Al prepared by hot oil column molding 2 O 3 Compared with the Fe-Al prepared by impregnation method using alumina as the carrier 2 O 3 , the distribution of Fe is more uniform.

[0020] 3. In the catalyst preparation process of the present invention, the metal salt is first mixed and dissolved in an acid solution, and then polyethylene glycol 2000 and citric acid are added, and the metal salt is completely dissolved by ultrasound to form a heterometallic coordination complex, and finally the metal is loaded by a pressurized stirring crystallization method. Compared with the traditional equal volume impregnation, the specific surface area of ​​the catalyst is effectively increased, and the dispersion of the loaded metal is improved and its affinity with Fe-Al is enhanced. 2 O 3 Interactions between carriers.

[0021] 4. The catalyst of the present invention does not contain K element. In the dehydrogenation of methylethylbenzene, in the presence of water vapor, there will be no phenomenon of K loss leading to catalyst deactivation.

[0022] 5. The catalyst of the present invention is used for the dehydrogenation reaction of methyl ethylbenzene, and the target product can be obtained under the condition that the water-to-hydrocarbon ratio is as low as 0.8, thereby solving the problems of high water-to-hydrocarbon ratio and rapid catalyst deactivation.

[0023] 6. The catalyst of the present invention has good performance under the condition of low water-to-hydrocarbon ratio, effectively improves the stability of the catalyst under the condition of low water-to-hydrocarbon ratio, and maintains good catalytic activity after continuous evaluation for 80 hours. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0025] Example 1

[0026] Step 1: Weigh 150g of low-sodium pseudo-boehmite prepared by the alcohol aluminum method, mix it with 195g of a 12% hydrochloric acid aqueous solution, stir it in a 70°C water bath for 2.5h at a stirring speed of 200r / min, and cool it to room temperature after stirring to obtain a crude aluminum sol. 110 mL of carbon tetrachloride was added to 100 mL of crude aluminum sol, stirred at room temperature for 2 h, then heated to 40°C at a heating rate of 3°C / min, stirred at constant temperature for 30 min, and allowed to stand for 12 h to obtain aluminum sol; at room temperature, 10 g of hexamethylenetetramine and 10 g of polyethylene glycol 2000 were added to the obtained aluminum sol and stirred for 2 h, 4.88 g of ferric nitrate nonahydrate was weighed and dissolved in 20 mL of deionized water and added to the aluminum sol, and stirred for 2 h, and the pH of the system was adjusted to 3-4 with a 10% hydrochloric acid aqueous solution to obtain Fe-modified aluminum sol; a hot oil column molding method was used to drop the Fe-modified aluminum sol into a hot oil column molding device, and alumina balls were collected at the lower end of the hot oil column, aged for 24 h under a nitrogen atmosphere at 2 MPa and 150°C, then washed with water until there was no obvious oil stain on the surface of the carrier, dried at 120°C, and finally calcined at 800°C for 4 h to obtain Fe-Al 2 O 3 The carrier has a specific surface area of ​​132m 2 / g, pore size is 15nm, and particle size is 1.6~1.8mm.

[0027] Step 2: Weigh 3.10g of cerium nitrate hexahydrate and 10.53g of magnesium nitrate hexahydrate and add them to 150g of 0.1mol / L hydrochloric acid aqueous solution, then add 1g of polyethylene glycol 2000 and 2.1g of citric acid, ultrasonicate for 40min to completely dissolve the solid to form a heterometallic Ce-Mg coordination complex, pour it into a high-pressure reactor with stirring and PTFE lining, and then add 100g of Fe-γ-Al 2 O 3 The carrier was stirred and crystallized at a pressure of 1.7 MPa and a temperature of 160°C for 12 hours, and the liquid in the system was evaporated by a rotary evaporator. The product was placed in a 100°C oven and dried to constant weight, and then calcined at 500°C for 2 hours in a muffle furnace, and finally reduced at 400°C for 2 hours in a hydrogen atmosphere to obtain a catalyst. The mass content of Ce and Mg in the catalyst is 1%, and the mass content of Fe is 0.6%, which is recorded as Ce 1 -Mg 1 / Fe 0.6 -γ-Al 2 O 3 .

[0028] Example 2

[0029] Step 1 of this embodiment is the same as that of Example 1. In step 2, 3.10 g of cerium nitrate hexahydrate and 2.95 g of calcium nitrate tetrahydrate are weighed and added to 150 g of 0.1 mol / L hydrochloric acid aqueous solution, and then 1 g of polyethylene glycol 2000 and 2.1 g of citric acid are added. Ultrasonication is performed for 40 min to completely dissolve the solid to form a heterometallic Ce-Ca coordination complex. The other steps of this step are the same as those of step 2 of Example 1 to obtain a catalyst. The mass content of Ce in the catalyst is 1%, the mass content of Ca is 0.5%, and the mass content of Fe is 0.6%, which is recorded as Ce. 1 -Ca 0.5 / Fe 0.6 -γ-Al 2 O 3 .

[0030] Example 3

[0031] Step 1 of this embodiment is the same as that of Example 1. In step 2, 5.22 g of gallium nitrate hexahydrate and 10.53 g of magnesium nitrate hexahydrate are weighed and added to 150 g of 0.1 mol / L hydrochloric acid aqueous solution, and then 1 g of polyethylene glycol 2000 and 2.1 g of citric acid are added. Ultrasonic treatment is performed for 40 min to completely dissolve the solid to form a heterometallic Ga-Mg coordination complex. The other steps of this step are the same as those of step 2 of Example 1 to obtain a catalyst. The mass content of Ga and Mg in the catalyst is 1%, and the mass content of Fe is 0.6%, which is recorded as Ga 1 -Mg 1 / Fe 0.6 -γ-Al 2 O 3 .

[0032] Example 4

[0033] Step 1 of this embodiment is the same as that of Example 1. In step 2, 1.55 g of cerium nitrate hexahydrate and 5.27 g of magnesium nitrate hexahydrate are weighed and added to 150 g of 0.1 mol / L hydrochloric acid aqueous solution, stirred until the solid is completely dissolved, and then 1 g of polyethylene glycol 2000 and 2.1 g of citric acid are added, and ultrasonic treatment is performed for 40 min to form a heterometallic Ce-Mg coordination complex. The other steps of this step are the same as those of step 2 of Example 1 to obtain a catalyst. The mass content of Ce and Mg in the catalyst is 1%, and the mass content of Fe is 0.6%, which is recorded as Ce 0.5 -Mg 0.5 / Fe 0.6 -γ-Al 2 O 3 .

[0034] Example 5

[0035] Step 1 of this embodiment is the same as that of Example 1. In step 2, 3.10 g of cerium nitrate hexahydrate and 5.27 g of magnesium nitrate hexahydrate are weighed and added to 150 g of 0.1 mol / L hydrochloric acid aqueous solution, and then 1 g of polyethylene glycol 2000 and 2.1 g of citric acid are added. Ultrasonication is performed for 40 min to completely dissolve the solid to form a heterometallic Ce-Mg coordination complex. The other steps of this step are the same as those of step 2 of Example 1 to obtain a catalyst. The mass content of Ce in the catalyst is 1%, the mass content of Mg is 0.5%, and the mass content of Fe is 0.6%, which is recorded as Ce. 1 -Mg 0.5 / Fe 0.6 -γ-Al 2 O 3 .

[0036] Example 6

[0037] Step 1 of this embodiment is the same as that of Example 1. In step 2, 1.55 g of cerium nitrate hexahydrate, 5.27 g of magnesium nitrate hexahydrate and 5.90 g of calcium nitrate tetrahydrate are weighed and added to 150 g of 0.1 mol / L hydrochloric acid aqueous solution, and then 1 g of polyethylene glycol 2000 and 2.1 g of citric acid are added, and the solid is completely dissolved by ultrasonic treatment for 40 min to form a heterometallic Ce-Mg coordination complex. The other steps of this step are the same as those of step 2 of Example 1 to obtain a catalyst. The mass content of Ce and Mg in the catalyst is 0.5%, the mass content of Ca is 1%, and the mass content of Fe is 0.6%, which is recorded as Ce. 0.5 -Mg 0.5 -Ca 1 / Fe 0.6 -γ-Al 2 O 3 .

[0038] Example 7

[0039] Step 1 of this embodiment is the same as that of Example 1. In step 2, 3.10 g of cerium nitrate hexahydrate and 5.90 g of calcium nitrate tetrahydrate are weighed and added to 150 g of 0.1 mol / L hydrochloric acid aqueous solution, and then 1 g of polyethylene glycol 2000 and 2.1 g of citric acid are added, and the solid is completely dissolved by ultrasonic treatment for 40 min to form a heterometallic Ce-Ca coordination complex. The other steps of this step are the same as those of step 2 of Example 1 to obtain a catalyst. The mass content of Ce and Ca in the catalyst is 1%, and the mass content of Fe is 0.6%, which is recorded as Ce 1 -Ca 1 / Fe 0.6 -γ-Al 2 O 3 .

[0040] Example 8

[0041] Step 1 of this embodiment is the same as that of Example 1. In step 2, 2.61 g of gallium nitrate hexahydrate and 5.27 g of magnesium nitrate hexahydrate are weighed and added to 150 g of 0.1 mol / L hydrochloric acid aqueous solution, and then 1 g of polyethylene glycol 2000 and 2.1 g of citric acid are added. Ultrasonication is performed for 40 min to completely dissolve the solid to form a heterometallic Ga-Mg coordination complex. The other steps of this step are the same as those of step 2 of Example 1 to obtain a catalyst. The mass content of Ga in the catalyst is 0.5%, the mass content of Mg is 1%, and the mass content of Fe is 0.6%, which is recorded as Ga 0.5 -Mg 1 / Fe 0.6 -γ-Al 2 O 3 .

[0042] Comparative Example 1

[0043] Weigh 3.10 g of cerium nitrate hexahydrate, 10.53 g of magnesium nitrate hexahydrate, and 4.34 g of ferric nitrate nonahydrate, add 95 g of deionized water, stir and dissolve, then pour in 100 g of commercially available γ-Al with a particle size of 1.6 to 1.8 mm. 2 O 3 (water absorption rate is 0.95), let it stand for 6 hours, put it in a 100℃ oven to dry to constant weight, then calcine it at 500℃ in a muffle furnace for 2 hours, and finally reduce it at 400℃ in a hydrogen atmosphere for 2 hours to obtain the catalyst, which is recorded as Ce 1 -Mg 1 -Fe 0.6 / γ-Al 2 O 3 .

[0044] Comparative Example 2

[0045] Weigh 3.10g of cerium nitrate hexahydrate and 2.95g of calcium nitrate tetrahydrate, add 95g of deionized water, stir and dissolve, then pour in 100g of Fe / γ-Al 2 O 3 The support (prepared in the same manner as in Example 1) was allowed to stand for 12 h, dried in an oven at 100 °C to constant weight, then calcined in a muffle furnace at 500 °C for 2 h, and finally reduced at 400 °C for 2 h in a hydrogen atmosphere to obtain a catalyst, which was recorded as Ce. 1 -Ca 0.5 / Fe 0.6 -γ-Al 2 O 3 (Ⅱ).

[0046] Comparative Example 3

[0047] Weigh 3.10g of cerium nitrate hexahydrate and 10.53g of magnesium nitrate hexahydrate and add them to 150g of 0.1mol / L hydrochloric acid aqueous solution, stir until the solid is completely dissolved, pour into a high-pressure reactor with stirring and PTFE lining, and then add 100g of Fe-γ-Al 2 O 3 The support was stirred and crystallized at a pressure of 1.7 MPa and a temperature of 160°C for 12 h. The liquid in the system was evaporated by a rotary evaporator. The product was placed in an oven at 100°C and dried to constant weight. It was then calcined at 500°C for 2 h in a muffle furnace and finally reduced at 400°C for 2 h in a hydrogen atmosphere to obtain a catalyst, which was recorded as Ce. 1 -Mg 1 / Fe 0.6 -γ-Al 2 O 3 (III).

[0048] Comparative Example 4

[0049] While stirring at room temperature, add 2L 0.6mol / L Al(NO 3 ) 3 Add ammonia water to the aqueous solution to adjust the pH to 8-9, continue stirring for 1 hour, and filter after the precipitation is completed to obtain γ-Al 2 O 3 Carrier. Weigh 3.62g Fe(NO 3 ) 3 9H 2 O was added into 60 mL of deionized water, stirred to dissolve, and then 50 g of γ-Al 2 O 3 The support was stirred at 40°C for 4 h, evaporated to dryness in a water bath at 80°C, and then dried at 120°C for 4 h. The obtained sample was calcined at 600°C for 4 h to obtain a catalyst, which was recorded as Fe 2 O 3 / γ-Al 2 O 3 .

[0050] The catalytic performance of the catalysts prepared in Examples 1 to 8 and Comparative Examples 1 to 4 was evaluated by dehydrogenating p-methylethylbenzene. The specific method was as follows: 10 mL of the catalyst was weighed and loaded into a fixed bed quartz reaction tube for evaluation. The evaluation conditions were: 620° C., normal pressure, a mass ratio of water vapor to p-methylethylbenzene of 2.5:1 and 0.8:1, respectively, and a liquid space velocity of 2 h -1 The separated reaction products were directly analyzed online by Agilent 7890A gas chromatograph equipped with a hydrogen flame detector (FID). The results of the conversion rate of p-methylethylbenzene and the selectivity of p-methylstyrene are shown in Tables 1 and 2.

[0051] Table 1 Initial 10 h evaluation results of various catalysts for dehydrogenation of p-methylethylbenzene to p-methylstyrene

[0052]

[0053] Table 2 Performance of each catalyst under low water-to-hydrocarbon ratio conditions for 80 hours

[0054]

[0055]

[0056] As can be seen from Table 1, the catalysts prepared by Examples 1 to 8 of the present invention effectively improve the catalytic activity of the catalyst in the application of dehydrogenation of p-methylethylbenzene to p-methylstyrene. When the catalyst of the present invention is used for the reaction of dehydrogenation of p-methylethylbenzene to p-methylstyrene, under the condition of a water-to-hydrocarbon ratio of 2.5:1, the conversion rate of p-methylethylbenzene exceeds 85% and the selectivity of p-methylstyrene is higher than 90% in the initial evaluation (10h), and when the water-to-hydrocarbon ratio is as low as 0.8:1, the catalytic performance is still similar to that under the condition of a water-to-hydrocarbon ratio of 2.5:1. As can be seen from Table 2, when the water-to-hydrocarbon ratio is 0.8:1, after continuous evaluation for 80h, the catalyst in the embodiment of the present invention still maintains good catalytic activity without obvious deactivation. By comparison with the comparative example, the present invention introduces active metal Fe during the preparation of the alumina carrier, and during the preparation of the catalyst, the target metal salt is mixed and dissolved in an acid solution, polyethylene glycol 2000 and citric acid are added, and after being completely dissolved by ultrasound, a heterometallic coordination complex is formed, which is then crystallized under pressure, which can effectively improve the activity of the catalyst and the yield of p-methylstyrene.

[0057] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solutions of the present invention can be simply modified and combined, but these simple modifications and combinations are also regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A potassium-free catalyst for preparing p-methylstyrene with a low water-to-hydrocarbon ratio, characterized in that: The catalyst uses γ-Al2O3 loaded with iron as a carrier, loaded with active metal and auxiliary metal; the active metal is any one or more of Ti, Ga, and Ce, and the auxiliary metal is any one or more of Ca, Mg, Zn, and Mo; in terms of mass percentage of the catalyst, the mass content of the active metal is 0.1% to 2%, the mass content of the auxiliary metal is 0.1% to 1.2%, and the mass content of Fe is 0.3% to 1%; The catalyst is prepared by the following steps: Step 1: Mix low sodium pseudo-boehmite with an acid solution, stir at 60-80°C for 2-3h to obtain a crude aluminum sol; add a non-polar solvent to the crude aluminum sol, stir at room temperature for 1-2h, then heat to 40-50°C at a heating rate of 1-3°C / min, stir at a constant temperature for 30-50min, and stand for 10-18h to obtain an aluminum sol; at room temperature, add a gelling agent to the aluminum sol and continue to stir for 1-2h, then add an aqueous solution of an Fe precursor thereto, continue to stir for 1.5-2h, and adjust the pH of the system to 3-4 with a 10% hydrochloric acid aqueous solution to obtain an Fe-modified aluminum sol; adopt a hot oil column molding method to subject the Fe-modified aluminum sol to a ball dropping, aging, water washing, drying, and roasting process to obtain an iron-loaded γ-Al2O3, which is recorded as a Fe-Al2O3 carrier; Step 2: dissolve the active metal precursor and the auxiliary metal precursor in a 0.1 mol / L hydrochloric acid aqueous solution, add polyethylene glycol 2000 and citric acid, and ultrasonicate for 30 to 60 minutes to form a heterometallic coordination complex, pour into a high-pressure reactor with stirring and a tetrafluoroethylene lining, and then add the Fe-Al2O3 carrier, stir and crystallize for 10 to 24 hours at a pressure of 1.5 to 2.0 MPa and a temperature of 150 to 180°C, and the obtained product is dried, calcined, and reduced in a hydrogen atmosphere to obtain a catalyst.

2. The potassium-free catalyst for preparing p-methylstyrene with a low water-to-hydrocarbon ratio according to claim 1, characterized in that: In step 1, the mass ratio of the low-sodium pseudo-boehmite to the acid solution is 1:1.1-1.5, the acid solution is an aqueous solution of any one of hydrochloric acid, nitric acid, acetic acid, and chloroacetic acid, and the mass concentration of the acid solution is 8%-15%.

3. The potassium-free catalyst for preparing p-methylstyrene with a low water-to-hydrocarbon ratio according to claim 1, characterized in that: In step 1, the volume ratio of the crude aluminum sol to the non-polar solvent is 1:1-3; the non-polar solvent is any one of toluene, carbon tetrachloride, and n-heptane.

4. The potassium-free catalyst for preparing p-methylstyrene with a low water-to-hydrocarbon ratio according to claim 1, characterized in that: In step 1, the gelling agent is at least one of hexamethylenetetramine, urea, polyethylene glycol 2000, and sodium carboxymethyl cellulose; the amount of the gelling agent added is 5% to 10% of the mass of the aluminum sol.

5. The potassium-free catalyst for preparing p-methylstyrene with a low water-to-hydrocarbon ratio according to claim 1, characterized in that: In step 1, the Fe precursor is ferric nitrate.

6. The potassium-free catalyst for preparing p-methylstyrene with a low water-to-hydrocarbon ratio according to claim 1, characterized in that: In step 1, the Fe-modified aluminum sol is formed into balls by hot oil column molding method, aged for 24 to 36 hours in a nitrogen atmosphere, 2 to 2.5 MPa, and 140 to 170° C., washed with water to remove surface oil stains, dried at 100 to 150° C., and calcined at 750 to 850° C. for 3 to 5 hours to obtain iron-loaded γ-Al2O3.

7. The potassium-free catalyst for preparing p-methylstyrene with a low water-to-hydrocarbon ratio according to claim 6, characterized in that: In step 1, the specific surface area of ​​the Fe-Al2O3 carrier is 120 to 150 m 2 / g, pore size is 14-17nm, and particle size is 1.6-1.8mm.

8. The potassium-free catalyst for preparing p-methylstyrene with a low water-to-hydrocarbon ratio according to claim 1, characterized in that: In step 2, the active metal precursor and the auxiliary metal precursor are nitrates of the corresponding metals, and the added amounts of polyethylene glycol 2000 and citric acid are 0.5% to 2% and 1.5% to 3% of the mass of the Fe-Al2O3 carrier, respectively.

9. The potassium-free catalyst for preparing p-methylstyrene with a low water-to-hydrocarbon ratio according to claim 1, characterized in that: In step 2, the calcination temperature is 400-600° C., and the calcination time is 2-6 hours; the reduction temperature is 350-450° C., and the reduction time is 2-5 hours.

10. A method for preparing p-methylstyrene by dehydrogenating p-methylethylbenzene, characterized in that: In a fixed bed reaction device, the catalyst according to any one of claims 1 to 9 is loaded, and p-methylethylbenzene is used as a raw material. In the presence of water vapor, the p-methylethylbenzene dehydrogenation reaction is carried out, the reaction temperature is 550 to 650° C., the reaction pressure is normal pressure, and the liquid space velocity is 0.5 to 5 h -1 , the mass ratio of water vapor to p-methylethylbenzene is 0.5 to 3:1.

Citation Information

Patent Citations

  • Catalyst for preparation of p-methyl styrene, and preparation method and application thereof

    CN105562024A

  • Dehydrogenation catalyst

    US4804799A

  • Dehydrogenation catalyst and process for preparing same

    US5376613A

Cited By

  • Copper-based catalyst for synthesizing methanol through carbon dioxide hydrogenation and preparation method of copper-based catalyst

    CN120479437A